“Factores presentes en el diagnóstico tardío del cáncer de mama en mujeres atendidas en el Instituto Regional de Enfermedades Neoplásicas Dr. Luis Pinillos Ganoza – 2018” - Castillo Castro, Vanesa Cecilia (2019)
ABSTRACT Objective: To determine what factors are present in the late diagnosis of breast cancer in women treated at the Regional Institute of Neoplastic Diseases "Doctor Luis Pinillos Ganoza ", during 2018. Methods: An observational, descriptive and cross-sectional study was carried out, with a sample consisting of 78 women with breast cancer with late diagnosis (stage III and IV). Variables were studied such as: Age, region of origin, socioeconomic factors, access to health services and previous knowledge about Breast Cancer prevention. For the data collection a survey of 22 questions was used based on the survey prepared by Sara Cecilia Suasnabar Reves of the year 2012. The answers were classified according to this Ordinal scale: Adequate level of knowledge and access to health services (12-17 points), intermediate level (6-11 points) and Low level (0-5 points). The latter being already considered as a risk factor. Results: The factors present in the late diagnosis of breast cancer were: Age between 40 and 69 years old: 64 patients (84%), marital status of married or cohabiting: 50 patients (64 , 10%), have a partner who lives at home: 37 patients (47.43%), complete primary education level: 17 patients (21, 80%), housewife occupation: 74 patients (94, 87 %), economic income less than 930 soles: 77 patients (98, 72%), SIS insurance: 73 patients (93, 59%), region of origin of La Libertad: 54 patients (69.23%), knowledge previous intermediate in breast cancer prevention: 37 patients (47, 44%) and little access to health services: 43 patients (55, 13%). Conclusion: Age between 40 to 69 years, marital status of married or cohabitant, conjugal union (Living with the couple at home), complete primary grade, being a housewife, low income, type of insurance SIS, provenance Freedom, degree of intermediate knowledge and poor access to health services were factors present in the late diagnosis of breast cancer.